Implementasi Profesi Kependidikan Dalam Meningkatkan Mutu Pendidikan - Adilla Aisyahrani; Fathurrahman Hendli Pamungkas; Khoirunnisa Fadilla Rambe; Nurul Anjani Daulay; Rahmad Riadi; Zahra Jannah; Inom Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
In this study the authors took the title of the implementation of the educational profession in improving the quality of education where the educational profession is an important point in the implementation of improving the competence of teachers to support the quality of education in schools. The educational profession is intended to improve the quality of education for teachers in Indonesia because among the many aspects that support the quality of educational processes and outcomes, the educational profession or educators and education personnel play the most important role in relation to improving the quality of education and educational outcomes. The teacher plays a central role in directing teaching and learning activities and is the vanguard who really determines how the learning process is carried out.